Estrategia de formación continúa para mejoramiento del desempeño del talento humano de los centros infantiles del buen vivir del cantón la maná provincia de Cotopaxi. - Pilatasig Sanchez, Yesica Lorena (2017)
The improvement of a service and being in line with the new needs and demands of society means continuous preparation in different personal areas, therefore it is important that each human being should be in search of a new learning, the lack of expertise in areas in the Which the educators of the children's centers of good living perform, makes their performance is not efficient and therefore their service lacks quality, it is thought advisable to design a strategy of continuous training for the educators to prepare and thus to carry out a work with effectiveness. In research we will use the qualitative paradigm because we will study reality in its natural context. With the research carried out, it will be possible to improve the knowledge of the educators and the improvement of work performance, thus achieving a positive impact on society.